Legal capacity and the mental health social worker role: an international comparison. Issue 2 (3rd April 2018) - Campbell, Jim; Brophy, Lisa; Davidson, Gavin; O'Brien, Ann-Marie
ABSTRACT: New capacity laws have been introduced to many jurisdictions over the last decade. These laws have substantially changed the way in which mental health social workers and other professionals approach decisions about, and for, clients. Most notably, there is now an expectation that mental health social workers engage more in supported decision-making to prevent the need for substitute decision-making. This article describes the legal and policy drivers that have led to these changes in practice, with a particular emphasis on the significance of the United Nations Convention on the Rights of Persons with Disabilities (the UNCRPD) and the importance of recovery approaches in mental health services. It then uses selected literature to explore the efficacy of the laws and decision-making in this area. The second part of the article identifies the role that mental health social workers can play in supporting legal capacity, drawing from the authors' experience and knowledge of mental health social work and law in four jurisdictions: Victoria, Australia; Ontario, Canada; England and Wales; and Northern Ireland. It is concluded that mental health and other social workers need to refine skills, knowledge and values to accommodate this paradigm shift in law, policy and practice.